Physiological responses to swimming while wearing a wet suit - Trappe, T. A.; Pease, D. L.; Trappe, S. W.; Troup, J. P.; Burke, E. R. (International Journal of Sports Medicine, 1996)
The purpose of this study was to examine the influence of three different wet suits on the oxygen uptake (VO(2)), minute ventilation (VE). and heart rate responses to front crawl swimming. Five male subjects swam at four velocities (0.90, 1.05, 1.18 +/- 0.01, 1.31 +/- 0.02 m.sec(-1)) in each of four swimming suit conditions in a swimming flume. Conditions were completed in random order using a conventional swimming suit (SS), a wet suit that covered the full body (FULL), a wet suit that left the arms exposed (LONG), and a wet suit that left the arms and lower legs exposed (SHORT). Water temperature was 26.5 +/- 1.0 degrees C for all trials. VO(2) and V(E) were decreased (p < 0.05) while swimming in the three wet suits as compared to the SS at all four velocities. VO(2) and V(E) were also lower (p < 0.05) in the FULL as compared to the SHORT at all four velocities; however, there were no differences between the SHORT and LONG or LONG and FULL at any of the velocities. Decreases in VO(2) from SS averaged 16.2 +/- 1.9 (SHORT), 22.8 +/- 2.4 (LONG), and 33.6 +/- 2.9% (FULL) over all four velocities. Similarly, reductions in V(E) from SS averaged 14.6+/- 1.5, 19.6 +/- 1.6, 24.2 +/- 1.5%, in the SHORT, LONG, and FULL, respectively. Heart rate and rating of perceived exertion were higher (p < 0.05) in the SS as compared to the three wet suits at 1.31 m.sec(-1) only. In conclusion, oxygen uptake and minute ventilation during swimming at a given velocity were decreased when wearing a wet suit as compared to a conventional swimming suit. Further, these decreases were related to the amount of wet suit covering the body.